PRELIMINARY ESTIMATION OF IGNEOUS ROCK RESERVE OF QUARRY MATERIALS USING GEOELECTRIC METHOD IN BIYUKU VILLAGE, BANGKO DISTRICT, JAMBI PROVINCE - Dwiyantoro, Rizky Ramadhan; Hanatha, Fauzi Daffa; Anugrah, Febry (JGE (Jurnal Geofisika Eksplorasi), 2025)
The earth's subsurface can be composed of various rocks such as igneous rocks, sedimentary rocks, and metamorphic rocks. Determination of rock types below the surface is carried out using geophysical methods. This study aims to identify Rhyolite-Andesite Rock using the 2D geoelectric method of the Wenner-Schlumberger configuration used in determining the initial reserves of Rhyolite-Andesite mining materials by utilizing subsurface resistivity values ​​based on 2D and 3D resistivity cross-section analysis. The results of the petrological analysis showed that the rock was rhyolite  lava rock which was interpreted to come from the Rhyolite-Andesite Volcanic Formation of the Quaternary age. Interpretation of resistivity values ​​is divided into 2 groups, namely values ​​<350 Ωm interpreted as weathered igneous rocks due to structure and groundwater, then values> 350 Ωm interpreted as fresh igneous rocks of quarry mining materials (rhyolite). Initial reserve estimates based on 3D resistivity model blocks with a cutoff value of > 350 Ωm interpreted as rhyolite igneous rock have reserves volume  584,595.9461 m3.